Estados excitados del Ba136 - Jorge Nassiff, Sonia; Urstein, Tauba; Peyre, Juan J. (Comisión Nacional de Energía Atómica (CNEA), 1959)
Fil:Jorge Nassiff, Sonia Comisión Nacional de Energía Atómica (CNEA). República Argentina